Time variation, asymmetry and threshold effect in Malta's Phillips curve - William Gatt (Central Bank of Malta, 2016)
This paper estimates a Phillips curve for Malta using data since the 1960s and presents evidence that the relationship has flattened over time, implying that the link between inflation and economic activity has weakened. Further analysis finds that this phenomenon was driven by downward price stickiness, whereby the responsiveness of price inflation is limited during economic slowdowns; however the Phillips curve was and remains alive during economic booms.
Keywords: C11; C32; E31; E32; O11; 330